2022
DOI: 10.1038/s41598-022-17954-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive bioinformatic analysis of MMP1 in hepatocellular carcinoma and establishment of relevant prognostic model

Abstract: Matrix metalloproteinase 1 (MMP1) encodes endopeptidases associated with degradation of multiple components of the extracellular matrix. This function has increasingly been considered to play a major proteolysis role in tumor invasion and metastasis. However, the relationship between MMP1 gene expression, tumor-immune microenvironment and prognosis in hepatocellular carcinoma patients remains mostly unclear. This study focused on a comprehensive analysis of MMP1 in hepatocellular carcinoma, specifically the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Combined with survival analysis and ROC curve analysis, we concluded that MMP1 expression was related to the prognosis of OS or DFS in CESC, GBM, HNSC, OV, and PAAD, and had high diagnostic value. In LIHC, MMP1 expression was associated with OS and DFS outcomes, which is consistent with a previous study ( 20 ). However, ROC curves showed that MMP1 didn’t have a high predictive accuracy in LIHC, and thus the prognostic role of MMP1 in HCC remained of concern.…”
Section: Discussionsupporting
confidence: 92%
“…Combined with survival analysis and ROC curve analysis, we concluded that MMP1 expression was related to the prognosis of OS or DFS in CESC, GBM, HNSC, OV, and PAAD, and had high diagnostic value. In LIHC, MMP1 expression was associated with OS and DFS outcomes, which is consistent with a previous study ( 20 ). However, ROC curves showed that MMP1 didn’t have a high predictive accuracy in LIHC, and thus the prognostic role of MMP1 in HCC remained of concern.…”
Section: Discussionsupporting
confidence: 92%
“…MMP-1 was expressed in many different malignant tumors higher than in corresponding normal tissues. 24 The transcription of MMP-1 is activated by AP-1, 23 including c-fos and c-jun . In hepatocellular carcinoma (HCC) patients, MMP-1 was upregulated and related to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…MMP1 is upregulated in patients with HCC and is associated with a poor prognosis. [42] Pharmacological inhibition and gene silencing of TRPA1 downregulates MMP1 production in osteoarthritis, [43] whereas activation of TRPV1 increases the expression of MMP1 . [44] However, in the present study, specific levels of TRPA1 and TRPV1 were not detected in HCC tissues.…”
Section: Discussionmentioning
confidence: 99%